2022
DOI: 10.13057/nusbiosci/n140207
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, floral phenology, and socio-economic importance of melliferous plants in Eastern Ethiopia

Abstract: Abstract. Fassil A, Habtamu T, Tahir M, Terefe T. 2022. Diversity, floral phenology, and socio-economic importance of melliferous plants in Eastern Ethiopia. Nusantara Bioscience 14: 172-181. Beekeeping is a supply of extra money and financial gain for many thousands of farmer beekeepers in Ethiopia and plays a big role in preserving natural resources. Honeybees and flowering plants have co-evolved in their special symbiotic relationship. Bee plant types and their flowering duration differ from one place to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Land-use changes and direct exploitation of plant resources also explain the decreased abundance of WEPs [ 91 – 93 ]. In addition, habitat destruction and overharvesting also pose significant impacts on wild plant resources [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Land-use changes and direct exploitation of plant resources also explain the decreased abundance of WEPs [ 91 – 93 ]. In addition, habitat destruction and overharvesting also pose significant impacts on wild plant resources [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…The traditional medicinal and other uses of plants extracted in this study, i.e., M. senegalensis Loes., A. vera (L.) Burm.f, N. physalodes (L.) Gaertn., Nicotiana tabacum L., Curcuma longa L., and P. dodecandra L’Hér. have been reported in Ethiopia [ [58] , [59] , [60] , [61] ].…”
Section: Discussionmentioning
confidence: 99%
“…), tabaco leaf ( Nicotiana tabacum L.), Turmeric rhzome ( Curcuma longa L.) and endod seeds ( Phytolacca dodecandra L’Hér.) has been reported in Ethiopia [ [58] , [59] , [60] , [61] ]. In vivo and in vitro studies have shown that A. vera species has several biological activities, such as antifungal, antioxidant and antiviral properties [ 62 ].…”
Section: Discussionmentioning
confidence: 99%